Islamic Religious Education from an Ontological Perspective: A Philosophical Study - Lutfiah Holifa Balkis; Mahmud Arif; Radhiyah Syauqi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
ENGLISH: Islamic Religious Education from an Ontological Perspective: A Philosophical Study Objectives: This study examines the ontological foundations of Islamic Religious Education (IRE), focusing on the nature of reality, human existence, knowledge, and educational aims within Islamic philosophical thought. Methods: A Systematic Literature Review (SLR) was conducted by synthesizing academic works published between 2015 and 2025 through systematic identification, screening, and thematic analysis. Results: The study reveals that IRE rests on a theocentric worldview that positions God as the ultimate reality; views humans as holistic beings with physical, intellectual, and spiritual dimensions; and regards knowledge as originating from divine revelation, supported by reason and experience. This ontological orientation strengthens curriculum development, clarifies the educator’s moral-spiritual role, and promotes the integration of religious and scientific knowledge. Conclusion: Ontological principles offer a comprehensive philosophical foundation for redefining educational aims, methods, and teacher roles, while restoring moral and spiritual direction in education. Contribution: This research provides a conceptual overview of IRE’s ontological structure, serving as a foundation for curriculum reform, teacher capacity building, and integrative educational models rooted in Islamic metaphysicsINDONESIAN: Pendidikan Agama Islam Dalam Perspektif Ontologi: Sebuah Kajian Filosofis.Tujuan: Penelitian ini bertujuan mengkaji landasan ontologis Pendidikan Agama Islam (PAI) dengan menelaah hakikat realitas, keberadaan manusia, pengetahuan, dan tujuan pendidikan dalam perspektif filsafat Islam. Metode: Penelitian menggunakan metode Systematic Literature Review (SLR) terhadap publikasi ilmiah tahun 2015–2025 melalui proses identifikasi, seleksi, dan analisis tematik. Hasil: Penelitian menunjukkan bahwa ontologi PAI berakar pada pandangan teosentris yang menempatkan Tuhan sebagai realitas tertinggi, manusia sebagai makhluk holistik, dan pengetahuan sebagai gabungan wahyu, akal, dan pengalaman. Pendekatan ini memperkuat kurikulum, peran pendidik, serta integrasi ilmu agama dan ilmu umum. Kesimpulan: Landasan ontologis memberikan kerangka filosofis komprehensif untuk merumuskan kembali tujuan, metode, dan struktur pendidikan Islam. Kontribusi: Penelitian ini menyajikan peta konseptual ontologi PAI sebagai dasar pengembangan kurikulum, peningkatan kompetensi pendidik, dan model pendidikan integratif berbasis prinsip metafisik Islam: